Child Health Status in Cameroon: Mitigating Role of Information Asymmetry - Aziseh Eric Njekang; Molem Sama Christopher; Mary Bi Suh Atanga (Law and Economy, 2023)
Prominent among others in agenda 2030 for Cameroon, is to guarantee that every child should have good health and live longer. Information asymmetry can be disadvantageous to child health status and strategies intended to address this worry can improve the child health status and consequently bring growth. This work analyses the mitigating effect of information asymmetry on child health status in Cameroon using data from the Cameroon Demographic Health Survey (CDHS) of 2018. The instrumental variable probit (ivprobit) approach is used to investigate this relation. The findings reveal that information asymmetry measured as an index has an adverse effect on child health status in Cameroon. Specifically, information asymmetry reduces the probability of child health status by 0.949 units. Other covariates that affect child health status in Cameroon include age, age squared, gender, level of education and place of residence. For Cameroon to improve on child health status through information flow, policies guided to increase the flow of health information are highly recommended by this study so that child health status can be improved upon. The use of radios and child health programs that can be in pidgin language and mother tongues should be put on air both for local and national radio stations in Cameroon.